2018
DOI: 10.4314/jfas.v9i2s.55
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of enzymatic hydrolysis of skipjack tuna by-product using protamex ®: a response surface approach

Abstract: The goal of this study was to optimize enzymatic hydrolysis of the dark flesh of skipjack tuna (Katsuwonus pelamis). Protamex® was concentrations (1%, 1.5%, 2%, 2.5% 40 to 60 o C and times of 2 to 6 h. The experiment was performed following a five second-order central composite design w coefficients of determination for degree of hydrolysis (R2 = 0.9674) and free tryptophan content (R2 = 0.9426) indicate the suitability of the design for predicting the responses. The optimum hydrolytic conditions predicted by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Having a smaller p value also suggested that the independent variables (hydrolysis time and enzyme concentration) significantly affect DH and FC. In the present study, the best-fit model for the FC is quadratic, which agrees with various studies suggesting the quadratic model is most appropriate for tuna samples (Motamedzadegan et al 2010;Herpandi et al 2018;Nguyen et al 2021). Similarly, the optimization of the foaming capacity of the yellowfin tuna red meat hydrolysates fitted the quadratic model (Parvathy et al 2018), as does the optimization of the foaming expansion of protein hydrolysates of oneknife unicornfish (Alolod and Nuñal 2018).…”
Section: Discussionsupporting
confidence: 90%
“…Having a smaller p value also suggested that the independent variables (hydrolysis time and enzyme concentration) significantly affect DH and FC. In the present study, the best-fit model for the FC is quadratic, which agrees with various studies suggesting the quadratic model is most appropriate for tuna samples (Motamedzadegan et al 2010;Herpandi et al 2018;Nguyen et al 2021). Similarly, the optimization of the foaming capacity of the yellowfin tuna red meat hydrolysates fitted the quadratic model (Parvathy et al 2018), as does the optimization of the foaming expansion of protein hydrolysates of oneknife unicornfish (Alolod and Nuñal 2018).…”
Section: Discussionsupporting
confidence: 90%
“…The industrial processing of fish for human consumption generates more than 60% of the by-products, but the amount may depend on the raw materials, processing methods, and ultimate products required [2]. This accounts for approximately three-quarters of the total weight [3]. During fish processing, by-products such as skin and scales, intestinal parts (mainly the viscera, air bladder, and gonads), head parts, bones, and fins are generated [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, rest raw materials (i.e., viscera and heads) of yellowfin tuna processing industry are under utilized [2,3]. Huge amounts of rest raw materials (about 450,000 tons per year) are generated from tuna processing industry [4]. The disposal of these wastes produces a major problem to the environment because of their odour and high moisture content when are dumped as commercial or domestic waste [1].…”
Section: Introductionmentioning
confidence: 99%